2021
DOI: 10.4236/as.2021.123012
|View full text |Cite
|
Sign up to set email alerts
|

Melon Seedlings Phytomass under Poultry Litter Biochar Doses

Abstract: The use of organic waste for the preparation of seedling substrates is an important environmental and economic option. In this perspective, substrates using biochar emerges as an alternative for seedling production due to their favorable physical and chemical characteristics. The present study aimed to evaluate the efficiency of doses of poultry litter biochar as a substrate constituent for the production and quality of the seedlings. The work was conducted in a semi protected environment, belonging to the Fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…It is worth noting that the substrate plays an important role in the obtaining of quality seedlings, as it must provide a favorable environment, favoring the adequate supply of water and air, and have an excellent texture, structure, pH, and fertility (Barros et al, 2017;Santos et al, 2022). Among the available alternative materials, it is found that biochar, with its benefits related to its properties (high porosity, high retention, and availability of water and high cation exchange capacity), favors the retention of nutrients, thereby avoiding their losses and the direct nutrient supply (Laurentino et al, 2021). Silva Júnior et al (2020), when using carbonized rice husk and biochar in watermelon seedlings, found an attenuating effect for salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the substrate plays an important role in the obtaining of quality seedlings, as it must provide a favorable environment, favoring the adequate supply of water and air, and have an excellent texture, structure, pH, and fertility (Barros et al, 2017;Santos et al, 2022). Among the available alternative materials, it is found that biochar, with its benefits related to its properties (high porosity, high retention, and availability of water and high cation exchange capacity), favors the retention of nutrients, thereby avoiding their losses and the direct nutrient supply (Laurentino et al, 2021). Silva Júnior et al (2020), when using carbonized rice husk and biochar in watermelon seedlings, found an attenuating effect for salt stress.…”
Section: Introductionmentioning
confidence: 99%